PENGARUH PENERAPAN SISTEM KERJA WORK FROM HOME (WFH) PADA MASA PANDEMI COVID-19 TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) BIMA - Syarifuddin; Mulyadin (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
The purpose of this study was to determine the effect of implementing the Work From Home (WFH) work system during the Covid-19 pandemic on the performance of employees of the Bima State Wealth and Auction Service Office (KPKNL). This type of research used associative, questionnaire data collection techniques with google form assistive media. The population in this study were all employees of the Bima State Wealth and Auction Service Office (KPKNL), totaling 39 employees, 33 civil servants and honorary 6. The sampling technique used was purposive sampling, so the sample in this study were all state civil servants (ASN), amounting to 33 people. Research site of the Bima State Wealth and Auction Service Office (KPKNL).